Obtención de ácido desoxirribonucleico (ADN) útil para análisis genético, a partir de uñas recortadas. - CERVANTES GONZALES, Jorge Luis (2013)
Obtaining deoxyribonucleic acid (DNA) is the starting point for most genetic analysis. Nails are an accessible source of DNA. The present communication reports the successful extraction of genomic DNA from fresh nails, as well as from nails collected a month before the extraction. Amplification in two different regions of the human beta-globin gene was achieved by of the polymerase chain reaction. The described method, is a simple, non invasive method. Nail clipping material may be considered a convenient material for genetic analysis. (Rev Med Hered 2003; 14:230-233).